A new dynamic modelling methodology of a force measuring system for hypersonic impulse wind tunnel. (November 2020) - Li, Shichao; Li, Kesi; Liu, Bokai; Gao, Hongli; Sun, Yi; Dai, Zhikun; Liu, Weixiong
Highlights: Formula between the dynamic characteristics and test accuracy. A high-precision dynamic modeling method of the force measurement system. Dynamic model of joint part based on uneven pressure distributions. Joint part has an important influence on the force measurement system. Abstract: This paper aims to improve the dynamic modeling accuracy of the whole complex assembly of the wind tunnel measuring system. First, an analytical formula describing the relationship between dynamic characteristics and test accuracy of the force measuring system (FMS) is derived, and the influence of dynamic characteristics on test accuracy is analyzed. Subsequently, the method of single component modeling in FMS is elaborated. Furthermore, a modeling of bolted joint based on uneven contact surface-pressure distribution is proposed. In order to verify the effectiveness of FMS dynamic modeling method proposed in this research, the calculated and experimental modes are compared. Comparison results show that these two modal modes of each order are very similar, and the error range of frequency between them is 0.5%–13.4%. Finally, the theoretical results are in good agreement with the experimental results, which confirms the validity of the proposed modeling method.